Joyce, Derrida, Lacan, and the trauma of history : reading, narrative and postcolonialism - Boheemen, Christine van (Cambridge University Press, 1999)
In Joyce, Derrida, Lacan and the Trauma of History, Christine van Boheemen-Saaf examines the relationship between Joyce's postmodern textuality and the traumatic history of colonialism in Ireland. Joyce's influence on Lacanian psychoanalysis and Derrida's philosophy, Van Boheemen-Saaf suggests, ought to be viewed from a postcolonial perspective. She situates Joyce's writing as a practice of indirect 'witnessing' to a history that remains unspeakable. The loss of a natural relationship to language in Joyce calls for a new ethical dimension in the process of reading. The practice of reading becomes an act of empathy to what the text cannot express in words. In this way, she argues, Joyce's work functions as a material location for the inner voice of Irish cultural memory. This book engages with a wide range of contemporary critical theory and brings Joyce's work into dialogue with thinkers such as Zizek, Adorno, Lyotard, as well as feminism and postcolonial theory.